Applied Discourse Research in Educational Settings: A Portfolio of Case Studies - Pablo Artero Abellan (Journal of Language Education (JoLE), 2025)
Discourse analysis has become a central tool for exploring how classroom practices, institutional structures, and pedagogical ideologies are constructed and reproduced through language and multimodal communication. Despite its theoretical richness, a disconnect remains between discourse frameworks and their practical application in everyday educational research. This article addresses that gap by presenting a portfolio of four case studies that apply Critical Discourse Analysis (CDA), multimodal analysis, and corpus-based methods across varied educational contexts. The studies include data from bilingual classrooms, teacher training modules, ESL instruction, and university-level workshops. Each case offers a distinct methodological design while collectively showcasing how discourse-analytic tools can reveal patterns of authority, inclusion, ideological framing, and pragmatic misalignment in educational settings. The findings emphasize the potential of discourse-based research to inform teaching practice, foster critical pedagogy, and expand methodological repertoires in educational inquiry.